Women freemasons in Hungary from the beginnings - Vári, László (REHMLAC +, Journal of Historical Studies of Latin American and Caribbean Freemasonry plus, 2020)
Resistance to women's freemasonry is slowly dissolving in Hungary. It was only after the change of regime (1990) that women's and mixed lodges of foreign origin were established in Hungary. In the history of Hungarian freemasonry there have been only three Hungarian women were initiated in the 18th century, two were admitted to lodges in the 19th century. The only female masonic-like organisation in Hungary, the Eastern Star, died shortly after its foundation. Despite the lack of tradition, today we can speak of a well-functioning mixed and a women's lodge.